Karakteristik Kewirausahaan dan Pengaruhnya Terhadap Keinginan Berwirausaha (Studi Kasus: Universitas Kristen Duta Wacana) - Sisnuhadi Sisnuhadi; Petra Surya Mega Wijaya (Jurnal Riset Manajemen dan Bisnis, 2008)
Entrepreneurship recently becomes essentials as an indicator of countrtes' economic development. Some developed countries such as America, (JK, France and Japan happen to be an obvious example on how economic development is significantly affected by the growth of ,entrepreneurship. Due toits significant effect, many believe that entrepreneurship can enhance the wealth of the community, create job opportunities, provide new products and services, and contribute large number of tax paid to the govemment. The objectives of this research are to identify entrepreneurship characteristics an^d to determine the effect of those characteristics on theintention to be an entrepreneur. The 100 students of Duta Wacana Christian University wilt be used as a sample, except for student on the depar-trnent of Theology. Using two methods of data analysis, namely, Cochran Test,,and Multiple Regression, the results shows six prevailing characte:ristics af entrepreneurship that are; 1) learn from past experiences, 2) self-goveming personality, 3) competitive personality, 4) challenge-seeker personality, 5) future oriented personality, and 6) motivation. Furtherrnore, the result also finds that amongst six characteistics, only challenge-seeker personality candemonst:rate significant effect on intention to be an entrepreneur.Keywords: Entrepreneurship characteristics, intention, Cochran, multipleregression